Optimizing transfusion therapy for survivors of Haemoglobin Bart's hydrops fetalis syndrome: Defining the targets for haemoglobin‐H fraction and "functional" haemoglobin level. (17th February 2022) - Amid, Ali; Barrowman, Nick; Odame, Isaac; Kirby‐Allen, Melanie
Summary: Owing to the unique pathophysiology of anaemia in haemoglobin Bart's hydrops fetalis (HBHF), a transfusion strategy based on beta‐thalassemia guidelines is suboptimal for chronically transfused HBHF patients. A more aggressive transfusion aimed at reducing the proportion of non‐functional HbH and improving the "functional" haemoglobin (f‐Hb) can lead to reduced haemolysis and improved tissue oxygenation. However, the optimal transfusion targets for these parameters are not yet defined. In this retrospective, longitudinal study on four chronically transfused patients with HBHF, we used receiver operating characteristic curves to find a pre‐transfusion f‐Hb of 106 g/l and a HbH of 16.1% to be the optimal thresholds to achieve a normal soluble transferrin receptor and lactate dehydrogenase, respectively.